Association studies on ghrelin and ghrelin receptor gene polymorphisms with obesity. - Gueorguiev, M; Lecoeur, C; Meyre, D; Benzinou, M; Mein, C; Hinney, A; Vatin, V; Weill, J; Heude, B; Hebebrand, J; Grossman, AB; Korbonits, M; et al. (2009)
Ghrelin exerts a stimulatory effect on appetite and regulates energy homeostasis. Ghrelin gene variants have been shown to be associated with metabolic traits, although there is evidence suggesting linkage and association with obesity and the ghrelin receptor (GHSR). We hypothesized that these genes are good candidates for susceptibility to obesity. Direct sequencing identified 12 ghrelin single-nucleotide polymorphisms (SNPs) and 8 GHSR SNPs. The 10 common SNPs were genotyped in 1,275 obese subjects and in 1,059 subjects from a general population cohort of European origin. In the obesity case-control study, the GHSR SNP rs572169 was found to be associated with obesity (P = 0.007 in additive model, P = 0.001 in dominant model, odds ratio (OR) 1.73, 95% confidence interval (1.23-2.44)). The ghrelin variant, g.A265T (rs4684677), showed an association with obesity (P = 0.009, BMI adjusted for age and sex) in obese families. The ghrelin variant, g.A-604G (rs27647), showed an association with insulin levels at 2-h post-oral glucose tolerance test (OGTT) (P = 0.009) in obese families. We found an association between the eating behavior "overeating" and the GHSR SNP rs2232169 (P = 0.02) in obese subjects. However, none of these associations remained significant when corrected for multiple comparisons. Replication of the nominal associations with obesity could not be confirmed in a German genome-wide association (GWA) study for rs4684677 and rs572169 polymorphisms. Our data suggest that common polymorphisms in ghrelin and its receptor genes are not major contributors to the development of polygenic obesity, although common variants may alter body weight and eating behavior and contribute to insulin resistance, in particular in the context of early-onset obesity.